HUMAN RESOURCE MANAGEMENT IN IMPROVING THE QUALITY OF EDUCATION AT MI PLUS WATULIMO TRENGGALEK - Salsabila Nahdiaturrosidah; Binti Maunah; Asrop Safi’i (Universitas Islam Kiai Haji Achmad Siddiq Jember, 2026)
Quality education will give rise to a well-educated golden generation. However, in reality, the quality of education in Indonesia has not been fully supported, as reflected in data from UNESCO’s Global Education Monitoring Report in 2016. This study aims to determine how human resource management contributes to improving the quality of education at MI Plus Watulimo Trenggalek. The research employed a qualitative case study approach, with data obtained through in-depth interviews, observations, and documentation. Data were analyzed through three stages: data condensation, data display, and conclusion drawing. The findings show that human resource management at MI Plus Watulimo is implemented effectively through four stages: human resource planning; recruitment and selection; human resource training and development; and human resource control. Several challenges arose in the training and development stage, particularly regarding the teachers’ motivation, as many of them were hesitant to participate independently and tended to wait for direct instructions from the headmaster. Systematic and structured human resource management is essential to producing teachers with a strong sense of responsibility toward their work, which in turn helps improve the overall quality of education.